1961
DOI: 10.1152/jappl.1961.16.2.215
|View full text |Cite
|
Sign up to set email alerts
|

Vestibular reactions during prolonged constant angular acceleration

Abstract: Six human subjects received stimuli of 2 deg/sec.2 for 45 seconds and 1.5 deg/sec.2 for 60 seconds. Direct-coupled amplification of corneoretinal potential was used to record eye movements. Although some subjects occasionally showed a rise and decline in the velocity of nystagmus during constant angular acceleration, typically, near-maximum velocity was attained in about 30 seconds with little subsequent gain or loss until acceleration ended. Routinely, nystagmus outlasted the subjective afterreaction. Departu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
33
1

Year Published

1974
1974
2013
2013

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(38 citation statements)
references
References 0 publications
4
33
1
Order By: Relevance
“…The hallmark of adaptation is the reversal of the response when the stimulus is removed, and so this interpretation is compatible with the reversal of nystagmus and the re-emergence and reversal of perception of rotation upon removal from the magnetic field seen in the current study. Identical behaviour is seen upon termination of constant angular acceleration [8] and constant galvanic vestibular stimulation [11], [12]. It is expected that if stimulus duration is shortened so too is the amount of adaptation and the reversal of the response upon stimulus termination will be attenuated or abolished.…”
Section: Discusssionmentioning
confidence: 94%
See 1 more Smart Citation
“…The hallmark of adaptation is the reversal of the response when the stimulus is removed, and so this interpretation is compatible with the reversal of nystagmus and the re-emergence and reversal of perception of rotation upon removal from the magnetic field seen in the current study. Identical behaviour is seen upon termination of constant angular acceleration [8] and constant galvanic vestibular stimulation [11], [12]. It is expected that if stimulus duration is shortened so too is the amount of adaptation and the reversal of the response upon stimulus termination will be attenuated or abolished.…”
Section: Discusssionmentioning
confidence: 94%
“…Although, unlike nystagmus, perception of rotation did not last for the entire duration of magnetic field exposure, this discrepancy in persistence is not unexpected. Studies have shown that during constant angular acceleration, perception of rotation disappears over a time period of the order of one minute despite partly decayed, but continuing nystagmus [8]. This also occurs during constant galvanic vestibular stimulation [c.f., 11,12], another stimulus thought to be analogous to constant angular acceleration [12].…”
Section: Discusssionmentioning
confidence: 99%
“…Collins and Guedry [1962] found the value of A max, under states of arousal to be 30% higher than Guedry and Lauver [1961]. Short conversa tions consisting of simple questions which require some thought appeared to be the best way of preventing a decline in response [Kileny et al, 1980].…”
Section: Discussionmentioning
confidence: 92%
“…Psychophysical data are qualitatively consistent with Figure 5.lc . Clark and Stewart (1968) and Guedry and Lauver (1961) used stimuli of the same magnitude (l.5°/sec 2) and found peak yaw rate perception at approximately 35 seconds and 24 seconds after stimulus onse t , respectively. The Ormsby model response to an identical stimulus is shown by Figure 5.2 and peaks abou t 27 secon ds af ter stimulus onse t. Th e response of Figure 5.lc is quite reasonable , although some adjustmen t of the input spectrum or noise/ si gnal ratio may be warran ted to create a sli ghtly slower response.…”
Section: Yaw Accelerationmentioning
confidence: 98%